2021
DOI: 10.1002/jts.22689
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dimensional and Categorical Approaches to Characterizing the Association Between Posttraumatic Stress Disorder and Future Suicide Attempts

Abstract: The present study compared the utility of categorical (i.e., diagnostic status) and dimensional (i.e., symptom severity) approaches to measuring posttraumatic stress disorder (PTSD) in predicting future suicide attempts among participants in a nationwide, longitudinal study of U.S. military veterans who were deployed in support of operations in Iraq or Afghanistan after the September 11, 2001, terrorist attacks (9/11) and were enrolled in Veterans Health Administration services (N = 1,649). Following an initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…These results also are in keeping with the movement to investigate distinctions related to the patterns of specific PTSD symptom clusters individuals endorse (Kerig, 2019). For example, Lee et al (2021) found that meeting the diagnostic criteria for the intrusions (termed "reexperiencing" in DSM-IV parlance) cluster was the least accurate indicator of suicide risk. Future studies that "unpack" this phenomenon and more directly examine the specific associations between suicide and the other symptom clusters-namely avoidance, NACM, and arousal-will be of interest.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…These results also are in keeping with the movement to investigate distinctions related to the patterns of specific PTSD symptom clusters individuals endorse (Kerig, 2019). For example, Lee et al (2021) found that meeting the diagnostic criteria for the intrusions (termed "reexperiencing" in DSM-IV parlance) cluster was the least accurate indicator of suicide risk. Future studies that "unpack" this phenomenon and more directly examine the specific associations between suicide and the other symptom clusters-namely avoidance, NACM, and arousal-will be of interest.…”
supporting
confidence: 75%
“…Segueing into critical issues regarding methodology, the next article in the special issue compares the utility of dimensional (i.e., diagnostic status) versus categorical (i.e., symptom severity) approaches to measuring PTSD in the context of predicting suicide attempts among military personnel (Lee et al, 2021). A key finding of the study is that diagnostic status served as a sensitive but not a specific nor accurate predictor of suicide attempts at two subsequent time points among the 125 participants in the study who engaged in such behavior.…”
mentioning
confidence: 99%
“…6 Compared with studies that analysed PTSD symptom severity, the results of this study are consistent with those of both Cooper et al, who found that positive PC-PTSD screening results were associated with an increased suicide mortality risk, 15 and Lee et al, who found that the risk of suicide attempts was higher for veterans with PTSD symptom levels above the diagnostic threshold. 18…”
Section: Discussionmentioning
confidence: 99%
“…18 Veterans whose PTSD symptoms satisfied the diagnostic criteria had a higher risk of future suicide attempts, but the risk was even higher for veterans with symptom levels above the diagnostic threshold. 18 This study underscores the importance of using diagnostic codes in conjunction with PTSD symptom severity assessments as potential indicators of suicide risk. However, the study did not use suicide mortality as a primary outcome and the sample ( n = 1649) was too small to accurately evaluate suicide risk.…”
mentioning
confidence: 94%
See 1 more Smart Citation